India’s Foreign Policy during Prime Minister Atal Bihari Vajpayee (British Journal of Multidisciplinary and Advanced Studies, 2024)
This paper examines Indian foreign policy under Atal Bihari Vajpayee in terms of realistic pluralism. It argues that since the 1998 nuclear test, India has developed a slightly different style of realistic foreign policy as a means to achieve its core interests. It is characterized by an emphasis on engagement with contemporary challenges such as neoliberal globalization, terrorism, the issue of disarmament, coping with the changing international order, the decline of multilateral institutions, and new regionalism, etc. To deal with all these issues, India adopted realistic pluralism to accelerate India's economic development and security interests, as well as enhance its status as an emerging power in the international system by continuously promoting its cherished values. This paper explains how a party with its rightist ideology occupies power at a time when Congress fails to deliver people's aspirations. It analyses the key arguments that have been presented in this framework and the way Bajpayee put them into practice. It concludes with the assessment of Bajpayee strategies and future prospects that it will deliver for Indian foreign policy.